Neuromuscular Blocking Agents and Monitoring in China: A Cross-Sectional Survey of Current Management - Wu, HaoTian; Lin, ZengMao; Zhou, RuiHao; Huang, SuiSui; Chen, LingJun; Su, Yang; Cheng, LuoNa; Zhang, Huan (Frontiers in Medicine, 2022)
Background: Accumulating evidence indicates that neuromuscular monitoring and effective reversal of neuromuscular block reduces the incidence of postoperative residual curarization (PORC) in the perioperative period. However, little is known about the recent use of neuromuscular blocking agents (NMBAs) and monitoring in China. This paper presents the results of a nationwide survey conducted to obtain information regarding the current management of NMBAs in China. Methods: A questionnaire was sent to Chinese anesthesiologists inviting them to participate in the study. The questionnaire was available through the wenjuanxing website, and the link was sent to 1488 anesthesiologists using the Wechat mini app. Results: The web-based survey consisted of 28 questions, and data were collected using an online tool. Between May 19, 2021 and June 16, 2021, 637 responses were collected (response rate = 42.8%). Only 10.2% of anesthesiologists reported using neuromuscular function monitors, and 6.59% of respondents reported that they had the relevant monitors in the operating room. A total of 71.11% of the respondents reported using only the postoperative clinical manifestation to estimate if the patient had recovered from the muscle relaxant. Sugammadex and neostigmine were used in 0.47% and 28.41% of hospitals, respectively. Conclusion: Although PORC is a potential safety issue, the frequency of using reversal agents and monitors remains extremely low in China. Surveys such as this are important to understand the use and application customs of NMBAs in China. Improving safety awareness is an important goal of work-training programs and medical education.